Repercussões agudas da ventilação não invasiva sobre o fluxo sanguíneo cerebral e a função cognitiva de pacientes com doença pulmonar obstrutiva crônica e indivíduos sadios - Almeida, Mirizana Alves de (2011)
Chronic obstructive pulmonary disease (COPD) is an important public health problem worldwide. In addition to the involvement of the respiratory system extrapulmonary organs may be affected. Little attention has been given to the neurocognitive impairment and to the cardiovascular co-morbidities in this disease. Noninvasive ventilation (NIV) is the first choice ventilatory support in the exacerbation of COPD but controversial results have been shown in stable disease. Considering the short-term physiological cardiopulmonary effects of NIV application it is likely that it may cause acute effects on the cerebral blood flow (CBF) and maybe on the cognitive function. Objective: To analyze the acute effects of NIV breathing on the CBF and on the cognitive function of COPD patients and healthy subjects. Methods: This is an experimental and quantitative study in patients with stable moderate to severe COPD and in healthy volunteers, aged 40 to 80 years-old. We used transcranial doppler to monitor the mean velocity of CBF (MCBFV) at the middle cerebral artery. The experimental protocol involved the administration of NIV (Bilevel= 14 / 4 cmH2O) for 1 hour. The MCBFV and cardiopulmonary variables were collected immediately before NIV, 5, 30 minutes and 1 hour during NIV breathing and 5 and 30 minutes after its removal. The partial pressures of arterial blood gases, PETCO2, alveolar dead space, respiratory rate (RR), tidal volume (TV), minute ventilation (VE), SpO2, heart rate (HR), mean systemic arterial pressure (MAP), arterial pH were measured. Cognitive function was assessed through a battery of tests (Digit Span, Codes, Visual Span, Trails A and B and Stroop Test). The cognitive tests were applied at least 15 days before the experiment and after 5 minutes of NIV withdrawal. The analysis for longitudinal data was done by means of a regression model with random effects and the Wilcoxon tests if appropriate. Results: We studied nine COPD patients (3 women and 6 men) and 12 healthy subjects (9 women and 3 men). NIV breathing resulted in significant reduction of the MCBFV (p = 0.014) with no significant differences between groups, returning to baseline after NIV removal. The NIV in two groups led to rapid decrease of the PETCO2, RR, HR with concomitant increases of the TV and VE. The PaO2 and MAP showed no influence of the NIV in both groups. The PaCO2 and the pH did not vary in the COPD patients, an effect associated to a higher alveolar dead space during NIV. In the healthy volunteers the PaCO2 was lowered and the arterial pH increased significantly. The application of NIV improved the cognitive performance in the healthy group on the trial B test (p = 0.020) and in the phase three of the Stroop test (0.033). No effects of NIV were noted in the cognitive tests performance of the COPD patients. Conclusion: The application of bilevel NIV for 1 hour reduced MCBFV in healthy subjects and in patients with COPD, this effect being reversible after NIV withdrawal. Only in healthy individuals these effects were in parallel with changes in the PaCO2. It is likely that additional mechanisms beyond PaCO2 reduction are involved in the reduction of MCBFV during NIV breathing in COPD patients. There was a slight improvement in the cognitive function in healthy volunteers just after NIV application, while any effect was noted on this aspect in patients with COPD.